Jumantara Dance Learning Using the Explicit Instruction Learning Model - Prehantini, Musfita Eka; Widyastono, Herry; Sukmawati, Fatma (Lembaga Penelitian dan Pendidikan Mandala, 2023)
Dance learning has an important urgency because it promotes cultural expression, respects traditional heritage, and enriches understanding of the arts. It also fosters discipline, teamwork, and creativity, and can be an effective tool in character education and mental well-being. The learning model is an important element of the learning strategy, therefore, this research aims to determine the results of Jumantara Dance Learning using the Explicit Instruction learning model for students at Sanggar Kampoeng Thengul. The research method used by researchers is a qualitative descriptive method. Data was collected through several techniques, namely 1) Observation 2) Documentation 3) Interviews, then analyzed descriptively to narrate findings in the field. The results of the research describe that learning Jumantara dance using the explicit instruction learning model has an influence on the achievement of students' learning activities at Sanggar Kampoeng Thengul. This can be seen from the enthusiasm of students in participating in Jumantara dance learning and can be seen from the test or assessment results obtained. students at Sanggar Kampoeng Thengul got an average score of 80 while the highest score was 95 and the lowest score was 75.